1D and 2D oxidized carbon nanomaterials on epoxy matrix: performance of composites over the same processing conditions. (28th November 2017) - Ramos-Galicia, Lourdes; Martinez-Hernandez, Ana Laura; Fuentes-Ramirez, Rosalba; Velasco-Santos, Carlos
Abstract: Oxidized multi-walled carbon nanotubes and graphene oxide were evaluated as reinforcements of an epoxy resin. The composites were synthesized at concentrations of 0.1, 0.5, and 1.0 wt% under the same processing conditions. Nanocomposites with graphene oxide at 0.5 wt% present the highest mechanical properties, reaching up to ~180%, and ~760% of improvement in tensile strength and tensile toughness with respect to neat epoxy. Nevertheless, composites with oxidized nanotubes exhibit a tendency to improve mechanical properties as load increases. Storage moduli diminish due to cross-linking density reduction in all nanocomposites. Difference in thermal degradation are not observed in composites in comparison with matrix. Dimension play an important role in mechanical properties, because each nanoreinforcement has different performance with the concentration.